RECONCEPTUALIZING TEACHING SKILLS FOR 21ST-CENTURY LEARNING: INTEGRATING 4C COMPETENCIES AND TECHNOLOGY-ENHANCED PEDAGOGY - Uswatun Hasanah; Era Afriza; M. Sirozi (Jurnal Konseling Pendidikan Islam, 2026)
Teaching skills constitute a fundamental component in supporting the development of 21st-century skills encompassing critical thinking, creativity, communication, and collaboration (4C). This study aims to examine how teachers' teaching skills can be optimized to develop 21st-century skills among students. Employing a qualitative descriptive method with a literature review approach, this research analyzes various academic sources related to learning strategies, teacher roles, and 4C skills implementation in classrooms. The findings demonstrate that teachers must transform from knowledge transmitters to learning facilitators capable of creating active, innovative, and student-centered learning environments. Effective teaching skills include instructional design, classroom management, methodological variation, reinforcement, and constructive feedback. Technology integration and process-based learning approaches prove capable of enhancing engagement and higher-order thinking abilities. However, the development of adaptive teaching skills faces systemic, individual, and contextual challenges that mutually reinforce one another. The conclusion emphasizes that mastery of adaptive and innovative teaching skills serves as the key foundation in preparing competent generations ready to navigate the challenges of the 21st century.